INGLIZ VA XITOY TILLARINING MORFOSINTAKTIK VA PRAGMATIK XUSUSIYATLARI: CHOG‘ISHTIRMA TADQIQOT - Khursanova Farida Farkhod kizi, (TADQIQOTLAR, 2025)
Abstract:  This  article  presents  a  comparative  investigation  of  English  and Chinese morphosyntax and pragmatics. The study analyzes the structural nature of both languages,  focusing  on  word  formation,  syntactic  patterns,  politeness  strategies, discourse organization, and the role of context in meaning construction. The results indicate that English demonstrates a hybrid analytic–synthetic structure, while Chinese is  strongly  isolating  and  heavily  context-driven.  These  differences  significantly influence  translation  accuracy,  second-language  acquisition,  and  intercultural communication practices.